2016
DOI: 10.18632/oncotarget.10482
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3-TACC3 fusion in solid tumors: mini review

Abstract: Fibroblast growth factor receptors (FGFR) are transmembrane kinase proteins with growing importance in cancer biology given the frequency of molecular alterations and vast interface with multiple other signaling pathways. Furthermore, numerous FGFR inhibitors in clinical development demonstrate the expanding therapeutic relevance of this pathway. Indeed, results from early phase clinical trials already indicate that a subset of patients with advanced tumors derive benefit from FGFR targeted therapies. FGFR gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 38 publications
1
106
1
Order By: Relevance
“…We discovered FGFR3-TACC3 (F3-T3) gene fusions in 3% of human glioblastoma 4 . Subsequent studies reported similar frequencies of F3-T3 in many other cancers, thus qualifying F3-T3 as one of the most recurrent fusions across all tumor types 5,6 . F3-T3 fusions are potent oncogenes that confer sensitivity to FGFR inhibitors but the downstream oncogenic signaling remains largely unknown 2,46 .…”
mentioning
confidence: 89%
“…We discovered FGFR3-TACC3 (F3-T3) gene fusions in 3% of human glioblastoma 4 . Subsequent studies reported similar frequencies of F3-T3 in many other cancers, thus qualifying F3-T3 as one of the most recurrent fusions across all tumor types 5,6 . F3-T3 fusions are potent oncogenes that confer sensitivity to FGFR inhibitors but the downstream oncogenic signaling remains largely unknown 2,46 .…”
mentioning
confidence: 89%
“…4D) NCI-H1581, A-204, HuH-7, NCI-H716, and RT112) with a variety of different FGFR alterations (Supplementary Table S4). In addition to gene amplification or overexpression, FGFRs can be constitutively activated by chromosomal rearrangement (7,28). However, FGFR gene translocations are rarely present in existing xenograft models derived from cancer cell lines.…”
Section: Jnj-42756493 Antitumor Activity Is Associated With Inhibitiomentioning
confidence: 99%
“…FGFR3 fusion genes are observed in 3% (3/114) of muscle‐invasive urothelial cancer . Therefore, clinical trials of FGFR inhibitors in urothelial cancer harboring FGFR3 fusion genes or point mutations are ongoing . The clinical relevance of FGFR3‐TACC3 has been suggested by the clinical report of JNJ‐42756493, a pan‐FGFR inhibitor, which exerts three out of four partial responses among patients with tumors harboring FGFR3‐TACC3 fusion genes .…”
mentioning
confidence: 99%
“…(11) Therefore, clinical trials of FGFR inhibitors in urothelial cancer harboring FGFR3 fusion genes or point mutations are ongoing. (12) The clinical relevance of FGFR3-TACC3 has been suggested by the clinical report of JNJ-42756493, a pan-FGFR inhibitor, which exerts three out of four partial responses among patients with tumors harboring FGFR3-TACC3 fusion genes. (13) In a subset of urothelial cancer patients harboring FGFR3 gene alternation (FGFR3 fusion gene and point mutation) treated with BGJ398, the overall response rate in 25 evaluable patients was 36% and included one unconfirmed complete response and eight partial responses.…”
mentioning
confidence: 99%